Strategi Pembelajaran Seni Budaya Musik di SMA Negeri 2 Lubuk Basung - Asiska Zeriani; Wimbrayardi Wimbrayardi (Universitas Palangka Raya, 2023)
The purpose of this study is to catalogue the art and music culture education approaches that are in use at SMA Negeri 2 Lubuk Basung. Aspects such as learning objectives, learning materials, methods, musical instruments, learning processes, and evaluation are examined in the musical arts learning activities. The participants in this qualitative descriptive study are SMA Negeri 2 Lubuk Basung eighth-grade students. The researcher assumes the role of the research instrument, supplemented by auxiliary tools such as mobile phones, cameras, and stationery. Data collection was conducted through a systematic review of pertinent literature, observation, interviews, and documentation. Data collection, data classification, data clarification, data analysis, data description, and data conclusion are all components of data analysis techniques. The findings of the study indicate that the teaching modules in the independent curriculum do not provide comprehensive guidance for learning planning, which is influenced by various conditions. Research findings indicate that music culture instructors at SMA Negeri 2 Lubuk Basung have implemented music arts learning strategies consisting of five stages: learning preparation strategies, learning management strategies, strategies for utilising learning media, strategies for implementing model methods and learning approaches, strategies for motivating students, and strategies for evaluative purposes. The purpose of this study is to catalogue the art and music culture education approaches that are in use at SMA Negeri 2 Lubuk Basung. Aspects such as learning objectives, learning materials, methods, musical instruments, learning processes, and evaluation are examined in the musical arts learning activities. The participants in this qualitative descriptive study are SMA Negeri 2 Lubuk Basung eighth-grade students. The researcher assumes the role of the research instrument, supplemented by auxiliary tools such as mobile phones, cameras, and stationery. Data collection was conducted through a systematic review of pertinent literature, observation, interviews, and documentation. Data collection, data classification, data clarification, data analysis, data description, and data conclusion are all components of data analysis techniques. The results of the research suggest that the instructional modules within the self-directed curriculum fail to offer exhaustive direction for the process of learning planning, which is subject to a multitude of factors. Research findings indicate that music culture instructors at SMA Negeri 2 Lubuk Basung have implemented music arts learning strategies consisting of five stages: learning preparation strategies, learning management strategies, strategies for utilising learning media, strategies for implementing model methods and learning approaches, strategies for motivating students, and strategies for evaluative purposes.